Boron/nitrogen substituted the staggered hetero-dimers: Fascinating intermolecular charge-transfer and large NLO responses. (October 2017) - Gao, Feng-Wei; Zhang, Feng-Yi; Zhong, Rong-Lin; Xu, Hong-Liang; Sun, Shi-Ling; Su, Zhong-Min
Abstract: Recently, the structure-property relationships of an attractive isomeric radical1 ( Phys. Chem. Chem. Phys., 2016, 18, 29041–29044) with famous phenalenyl (PLY ) was investigated. CanPLY and1 form stable π-dimers? The single point energy scan result shows that the staggered π-dimer (2 ) has the lowest energy. In order to explore intermolecular charge-transfer and nonlinear optical property, two π-dimers (2a and2b by boron and nitrogen atoms substituting the central carbon atoms of2 ) are designed.2 has smaller intermolecular charge-transfer (0.020) and the first hyperpolarizability ( β tot, 3.18 × 10 2 au). However, boron and nitrogen substitution effect can greatly enhance intermolecular charge-transfer (0.215 for2a and 0.181 for2b ) and the β tot values (6.32 × 10 3 for2a and 6.80 × 10 3 for2b ). Interestingly, the β tot values of2a and2b are close to each other, but their β z components and the NBO charge analysis show that2a and2b have opposite direction of charge transfer, which can be well explained by the difference of the dipole moment component (Δ μ z ) between the ground and the excited states. Further, the first hyperpolarizability density study clearly substantiates the difference in their β zzz values: negative contribution for2a is much larger than positive contribution, while the first hyperpolarizability density for2b shows much larger positive contribution. Thus, the primary component of β zzz is negative value for2a and β zzz is positive value for2b . Combining with the frontier molecular orbital (FMO) and the electron density difference map (EDDM), intermolecular charge-transfer transition from B substituted fragment to N substituted fragment for2a and2b is concluded. The significant structure-property relationships in present π-dimers are beneficial for further theoretical and experimental investigations of high-performance nonlinear optical materials. Graphical abstract: The effect of boron and nitrogen substitution induces intermolecular charge-transfer, which significantly enhance second-order NLO properties of hetero-dimers with the aid of the DFT calculations. Highlights: PLY and its isomer1 radicals can form stable hetero-dimers. The effect of boron and nitrogen substitution induces intermolecular charge-transfer. Larger intermolecular charge-transfer significantly enhance second-order NLO properties. The first hyperpolarizability density study clearly substantiates the difference in their β zzz values.